INTERVIEW WITH BRITISH CONDUCTOR PAUL MANN - GOCAN, Andrei (Studia Universitatis Babes-Bolyai Musica, 2023)
British conductor Paul Mann is a regular guest with many major orchestras throughout Europe, the US, Australia, and the Far East. Orchestras with which he has worked include the London Symphony Orchestra, Royal Liverpool Philharmonic, Royal Scottish National Orchestra, Netherlands Radio Philharmonic, St Petersburg Philharmonic, RAI Torino, Orchestra dell’Arena di Verona; the BBC Orchestras, City of Birmingham Symphony, Hallé, among many others. Mr Mann has guest-conducted extcollaborations with USA and is a regular guest with the New York City Ballet. Projects with the LSO included collaborations the legendary rock group Deep Purple in two widely acclaimed performances of Jon Lord’s Concerto for Group and Orchestra at the Royal Albert Hall, the live DVD and CD which remain international bestsellers. Paul Mann was chief conductor of the Odense Symphony Orchestra in Denmark until 2008 and has made numerous critically acclaimed recordings for labels such as Bridge, Warner Classics, Da Capo, EMI, and Toccata Classics.